Temporal patterns of low frequency biological sounds in the Tubbataha Reef Natural Park in Cagayancillo, Palawan, Philippines - Durante, Edrine Jay L. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Studies on marine soundscapes are used in assessing the ecological integrity of a site. Recently, increase in anthropogenic pressures has compounded biodiversity loss which is alarming. This is why conservation management has become a research hotspot. This study uses the Acoustic Complexity Index (ACI) and the Normalized Difference Soundscape Index (NDSI) in observing temporal patterns of low frequency biological sounds. The indices were derived from underwater sound recordings spanning from May-July 2019 in the Tubbataha Reefs Natural Park in Cagayancillo, Palawan, Philippines. Spectrograms revealed that during May, lower frequency biological sounds were dominant compared to June and July. However, stronger signals were observed in May during the four-day comparison of spectrograms due to a consistency in the frequency range. A nocturnal and crepuscular increase in ACI and NDSI were observed during the entirety of the recording period using the subsampled data with specific time periods. Using NDSI, this paper suggests a low influence of anthropogenic noise in the recordings based on the set parameters.